Nrf2 pre-recruitment at Enhancer 2 is a hallmark of H2O2-induced epigenetic transcriptional memory in the HMOX1 gene in human umbilical artery endothelial cells - Carrasco-Wong, Ivo; Längst, Gernot; Sobrevia, Luis [UNESP]; Casanello, Paola (Wiley, 2024)
Maternal obesity (MO) is a significant cause of increased cardiometabolic risk in offspring, who present endothelial dysfunction at birth. Alterations in physiologic and cellular redox status are strongly associated with altered gene regulation in arterial endothelium. However, specific mechanisms by which the pro-oxidant fetal environment in MO could modulate the vascular gene expression and function during the offspring's postnatal life are elusive. We tested if oxidative stress could reprogram the antioxidant-coding gene's response to a pro-oxidant challenge through an epigenetic transcriptional memory (ETM) mechanism. A pro-oxidant double-hit protocol was applied to human umbilical artery endothelial cells (HUAECs) and EA.hy 926 endothelial cell lines. The ETM acquisition in the HMOX1 gene was analyzed by RT-qPCR. HMOX1 mRNA decay was evaluated by Actinomycin-D treatment and RT-qPCR. To assess the chromatin accessibility and the enrichment of NRF2, RNAP2, and phosphorylation at serin-5 of RNAP2, at HMOX1 gene regulatory regions, were used DNase HS-qPCR and ChIP-qPCR assays, respectively. The CpG methylation pattern at the HMOX1 core promoter was analyzed by DNA bisulfite conversion and Sanger sequencing. Data were analyzed using two-way ANOVA, and p < 0.05 was statistically significant. Using a pro-oxidant double-hit protocol, we found that the Heme Oxygenase gene (HMOX1) presents an ETM response associated with changes in the chromatin structure at the promoter and gene regulatory regions. The ETM response was characterized by a paused-RNA Polymerase 2 and NRF2 enrichment at the transcription start site and Enhancer 2 of the HMOX1 gene, respectively. Changes in DNA methylation pattern at the HMOX1 promoter were not a hallmark of this oxidative stress-induced ETM. These data suggest that a pro-oxidant milieu could trigger an ETM at the vascular level, indicating a potential epigenetic mechanism involved in the increased cardiovascular risk in the offspring of women with obesity.
Keywords: epigenetics; HMOX1; human endothelium; NRF2; oxidative stress; transcriptional memory